Community Outreach and FGD for Women MSE Empowerment: Entrepreneurial Orientation, Financing Access, and Halal Certification - Triandhari, Risna; Raden Parianom (Edumedia Solution, 2026)
Women-owned Micro and Small Enterprises (MSEs) play a strategic role in local economic development, yet face persistent challenges including limited managerial capacity, restricted access to financing, and low awareness of halal certification as a competitive strategy. This community service program aimed to enhance the understanding of MSE performance determinants, foster entrepreneurial orientation, and increase halal certification adoption intent among women MSE entrepreneurs in Cibinong, Bogor Regency. The program was delivered through outreach sessions and Focus Group Discussion (FGD) involving 25 women MSE entrepreneurs selected through purposive and snowball sampling. Pre-test and post-test evaluations were administered to measure knowledge gains and behavioral intent. Results demonstrated significant improvements: prior to the program, only 16% of participants held halal certification and 76% lacked systematic understanding of business performance factors. Following the intervention, 88% expressed intent to obtain halal certification and all participants successfully identified key MSE growth factors including entrepreneurial orientation, owner capacity, human resource quality, social capital, financing access, and government support. Collective strategic recommendations were also formulated through the FGD. These findings confirm that informational barriers—rather than lack of motivation—are the primary obstacle to MSE improvement, and that community-based outreach combined with participatory discussion is an effective empowerment approach.